A randomized comparison of oral chloroquine and sulfadoxine-pyrimethamine for the treatment of uncomplicated Plasmodium falciparum malaria in Laos - Mayfong Mayxay (2018)
Between June and October 2000 we conducted the first randomized trial in Laos comparing chloroquine (CQ) with sulfadoxine-pyrimethamine (SP) in the treatment of uncomplicated Plasmodium falciparum malaria (n = 29, 42-d follow-up, age > 5 years). The proportion of patients with treatment failure was high (CQ = 78%, RIII 46%; SP = 36%, RIII 15%). The treatment policy for uncomplicated P. falciparum malaria in Laos needs to be reviewed urgently. © 2003 Royal Society of Tropical Medicine and Hygiene.